PERBANDINGAN ANGKA PENDING KLAIM RAWAT JALAN BPJS KESEHATAN BERDASARKAN LIMA KATEGORI PENYEBAB UTAMA: TINJAUAN DATA TIGA BULAN TERAKHIR - Mulyana; Masriani Situmorang; Nimas Esya Bayazid; Hanifah Cahyani; Dinda Farizha (Journal of Hospital Administration and Management (JHAM), 2026)
Healthcare services through the National Health Insurance Program (JKN) require hospitals to manage the BPJS Kesehatan claims process accurately and timely, as delays or refunds can impact the continuity of hospital operations. One unit that plays a crucial role in this process is the Casemix Unit, which is responsible for grouping diagnoses and medical procedures and submitting claims based on BPJS Kesehatan regulations. This study aims to analyze the causes of the return of BPJS Kesehatan patient claim files for outpatient services at Awal Bros Gajah Mada Hospital. This study used a qualitative method with a descriptive approach, with Casemix Unit officers as the subjects and pending BPJS Kesehatan outpatient claim files as the objects. The results showed that of the 47,317 outpatient claim files from October–December 2024, 5,911 files (11.11%) were pending. The main causes of pending claims included incomplete required documents, inaccurate coding of diagnoses and medical procedures, problems with service episodes, and discrepancies between medical records and supporting examination results. The conclusion of this study indicates that completeness of files and accurate coding play a crucial role in the smooth processing of BPJS Kesehatan claims, necessitating increased coordination and accuracy in the outpatient claims management process.